Planar multifrequency mid-IR microwave-pumped lasers. (March 2020) - Mineev, A.P.; Nefedov, S.M.; Pashinin, P.P.; Goncharov, P.A.; Kiselev, V.V.; Stel'makh, O.M.
Abstract: The characteristics of planar repetitively pulsed diffusion-cooled HF, DF, HF – DF, Xe, and HF – DF – Xe(Kr) lasers pumped by a microwave discharge (2.45 GHz) are studied depending on the pump pulse duration (10 – 40 μs) and repletion rate (50 – 400 Hz), as well as on the composition and pressure of the working gas mixture (30 – 200 Torr) at low (to 0.6 L s −1 ) gas flow rates. It is demonstrated for the first time that a HF – DF – Xe gas-discharge laser may simultaneously operate as a HF – DF chemical molecular laser and a recombination laser based on xenon atom transitions and generate broadband (octave) radiation in the range 2.0 – 4.2 μm with an average output power of 43 mW and an efficiency of 0.9 %. With substitution of xenon for krypton, lasing in a HF – DF – Kr laser is obtained at wavelengths of 2.52 – 4.15 μm. Lasing in a HF – DF laser was achieved simultaneously in two spectral regions (2.7 – 2.9 and 3.6 – 4.2 μm) with an output power of ∼50 mW. It is found that a decrease in the pump pulse duration with a simultaneous increase in the pulse repletion rate for retaining the average energy deposition leads to an increase in the average output power and efficiency of the laser. At low pulse repetition rates (50 – 100 Hz) and a low gas mixture flow rate, helium buffer gas can be effectively substituted for neon. Operation of the Xe laser was achieved in the spectral range 2.03 – 3.65 μm with an average output power of 580 Mw at a pump pulse duration of 20 μs, a pulse repetition rate to 10 kHz, and a maximum efficiency of 55 %. The obtained experimental results demonstrate the possibility of creating broadband HF – DF – Xe lasers emitting in the frequency range 2 – 4 μm with a desired ratio of intensities in different spectral ranges.